2020
DOI: 10.1177/0961000620907961
|View full text |Cite
|
Sign up to set email alerts
|

Collection development practices in academic libraries in Tanzania

Abstract: The aim of this study was to assess the collection development practices in academic libraries in Tanzania. Specifically, the study examined the collection development practices and factors that influence these practices. The study involved four academic libraries and employed both qualitative and quantitative methods for data collection and analysis. Primary data were collected through informant interviews, observations and questionnaires methods. The study involved 44 library staff who filled in self-adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The current study further established that high demand from users and their ever-changing needs, inadequate professional staffing and library consortium arrangement were additional challenges experienced in University of Nairobi library. These findings concur with Mwilongo et al (2020) findings that due to associated challenges of underfunding and inadequate budget, understaffing as well as lack of professional development continue to exist. Regarding the challenges faced in the selection of information materials, the study revealed that lack of cooperation from teaching staff in the selection of materials to be purchased was the major challenge.…”
Section: Discussion Of Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…The current study further established that high demand from users and their ever-changing needs, inadequate professional staffing and library consortium arrangement were additional challenges experienced in University of Nairobi library. These findings concur with Mwilongo et al (2020) findings that due to associated challenges of underfunding and inadequate budget, understaffing as well as lack of professional development continue to exist. Regarding the challenges faced in the selection of information materials, the study revealed that lack of cooperation from teaching staff in the selection of materials to be purchased was the major challenge.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…Khan and Bhatti (2016) argues that in developing countries, inadequate funding is the major problem academic libraries are facing. The same finding is corroborated by Mwilongo et al (2020), who observe that the main problem facing most academic libraries in developing countries is inadequate budget allocation, which results to collection development activities including selection, acquisition and evaluation being subsequently affected. The current study further established that high demand from users and their ever-changing needs, inadequate professional staffing and library consortium arrangement were additional challenges experienced in University of Nairobi library.…”
Section: Discussion Of Findingsmentioning
confidence: 61%
“…Academic library is essential for higher education institutions in supporting teaching, studies, and information needs (Gabbay & Shoham, 2019;Mierzecka & Suminas, 2018). Many academic libraries have developed various resources to serve the needs of their institutions, including personnel training and the provision of digital -based equipment to access information effectively (Ayoung, Baada, & Baayel, 2021;Bamidele, Omeluzor, Imam, & Amadi, 2013;Hamad, Tbaishat, & Al-Fadel, 2017;Mwilongo, Luambano, & Lwehabura, 2020;Onyeneke & Ahaneku, 2021; These capabilities are necessary to navigate the 21st century, where high-quality services to stakeholders should be prioritized.…”
Section: Introductionmentioning
confidence: 99%
“…Collection development is an evolving concept of collection management that was devised to meet the changing demands of library users on collections (Bonaya, 2023;Mwilongo et al, 2020). Collection development involves several activities related to building and managing of variety of information resources to meet the desperate needs of users (Kamau & Elegwa, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Collection development involves several activities related to building and managing of variety of information resources to meet the desperate needs of users (Kamau & Elegwa, 2022). These activities include the assessment of users' needs, formulation and application of collection development policy, preparation of budget and fund management, selection and acquisition of materials in all formats, evaluation of materials to ascertain the extent they can meet the users' needs, planning for resources sharing and cooperative collection development activities, as well as promoting the use of library resources (Gulnaz & Fatima, 2019;Johnson, 2018;Mwilongo et al, 2020). Collection development also includes tools like publishers' catalogues, current trade bibliographies, National bibliographies, vendors list, discipline-based journals, suggestions from users, and so on (Mwilongo, 2020;Mwilongo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%